2013
DOI: 10.1007/s00192-013-2267-8
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, prospective, randomised, double-blind study to measure the treatment effectiveness of abobotulinum A (AboBTXA) among women with refractory interstitial cystitis/bladder pain syndrome

Abstract: For chronic refractory IC/BPS patients, AboBTXA was associated with no overall improvement in total OLS score, although significant benefit was noted in a small number of patients. The absence of posttreatment UTI was associated with a better response to AboBTXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 17 publications
0
66
0
Order By: Relevance
“…In the American Urological Association Guideline, 3 cystoscopy is the third-line treatment, but transurethral fulguration is recommended as a "should-be-performed" treatment for Hunner lesion. 4 In the standardization of terminology in Chronic Pelvic Pain, which will be published by the International Continence Society in the near future, IC/BPS will be divided into three groups: (i) without glomerulation; (ii) with glomerulation; and (iii) Hunner lesion. It is…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…In the American Urological Association Guideline, 3 cystoscopy is the third-line treatment, but transurethral fulguration is recommended as a "should-be-performed" treatment for Hunner lesion. 4 In the standardization of terminology in Chronic Pelvic Pain, which will be published by the International Continence Society in the near future, IC/BPS will be divided into three groups: (i) without glomerulation; (ii) with glomerulation; and (iii) Hunner lesion. It is…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…3 However, the efficacy of this treatment is still controversial, partly because of a limited number of RCT. 4 Furthermore, in most of those RCT, BoNT-A was administered with HD carried out simultaneously or shortly before, with the control arm receiving intravesical therapies, such as HD or BCG. 4,5 No studies have yet examined the effect of BoNT-A injection alone, not involving endoscopic or intravesical interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the trials included, 4 reported BCG compared with placebo [32][33][34][35], 3 evaluated BoNTA in comparison with placebo [8,36,37], 2 reported RTX compared with placebo [38,39], 2 comparatively assessed chondroitin sulfate and placebo [7,40], 2 reported PPS compared with placebo [5,41], 1 evaluated lidocaine compared with placebo [42], 1 reported oxybutynin compared with placebo [43], and 1 assessed BCG in comparison with BoNTA [44]. The studies included assessed 905 patients in all.…”
Section: Resultsmentioning
confidence: 99%
“…One study had a three-arm design, and included 0.05 μM RTX, 0.1 μM RTX, and placebo control groups [38]; another study had a four-arm design, and included 0.01 μM RTX, 0.05 μM RTX, 0.1 μM RTX, and placebo control groups [39]. Five studies identified additional treatments in both groups, including hydrodistention [8,37], oral PPS [5,41], and antibiotics [45]. The shortest and longest follow-up times were 29 days and 24 months respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%